Simulations of Wave Propagation and Wave–wave Interactions in the Solar Corona and Solar Wind - Nyberg, Seve (My University, 2021)
Several numerical methods, notably upwind schemes, Lax–Wendroff schemes, and a semi-Lagrangian scheme, are investigated in order to find suitable models to simulate Alfvén wave transport and evolution. The tools are assessed by comparing the simulation results of open magnetic field line settings to analytical solutions of the simulation problems. The most promising model found is a semi-Lagrangian scheme, due to its accuracy and computational efficiency, but it is currently limited to time invariant wave velocities. As an option to the semi-Lagrangian scheme the conservative Lax–Wendroff scheme was found to reproduce analytically solved results with a good accuracy. The semi-Lagrangian scheme is used to investigate wave–wave interactions in a closed magnetic field line setting, a coronal loop. The coronal loop setting is heavily simplified in order to observe the effects of wave–wave interactions on the spectra. The wave–wave interactions discussed are of the smallest order approximation level: three-wave interactions comprising of Alfvén waves and a sound wave. The three-wave interactions can clearly be seen altering the wave energy density spectra injected. The results may have implications in particle transport, and as such are interesting results to be investigated more. The simulation methods used are deemed sufficient, albeit improvements can be made, and as such are capable of simulating Alfvén wave spectra that are an important part of simulating particle acceleration in the solar corona.

Tutkielmassa etsitään tarkkaa ja tehokasta numeerista menetelmää Alfvénin aaltojen etenemisen ja vuorovaikutusten mallintamiseen. Etenemisen mallinukseen kehitettiin ylätuulimenetelmiä, Lax-Wendroff-menetelmiä ja puolilagrangelainen menetelmä. Menetelmien soveltuvuutta arvioidaan vertailemalla simulaatiotuloksia analyyttisiin tuloksiin koronan ja aurinkotuulen avoimella magneettikenttäviivalla. Lupaavimmaksi simulaatiomalliksi osoittautuu puolilagrangelainen menetelmä, jota kuitenkin rajoittaa vaatimus aaltojen nopeuksien aikariippumattomuudesta. Vaihtoehtoinen lupaava menetelmä on konservatiivinen Lax-Wendroff-menetelmä, joka toistaa kohtuullisen tarkasti analyyttisia tuloksia ja sallii ajasta riippuvat aaltonopeudet. Aalto-aalto-vuorovaikutuksia tutkitaan koronan suljetulla magneetikenttäviivalla käyttäen puolilagrangelaista menetelmää. Plasman ominaisuuksia kenttäviivaa ympäröivässä koronan silmukassa yksinkertaistetaan, jotta aaltospektrien muutosten tiedetään johtuvan aalto-aalto-vuorovaikutuksista. Aalto-aalto-vuorovaikutukset käsitellään matalimman kertaluokan approksimaatioina, kolmiaaltovuorovaikutuksina, joissa kaksi Alfvénin aaltoa ja ääniaalto vuorovaikuttavat keskenään. Kolmiaaltovuorovaikutusten huomataan selvästi muuttavan aaltojen energiatiheysspektrejä. Tuloksilla on vaikutusta ainakin varattujen hiukkasten kuljetukseen koronan silmukoissa. Tämän osalta jatkotutkimukset ovat tarpeen. Tutkitut simulaatiomenetelmät ovat riittäviä simuloimaan Alfvénin aaltojen spektrejä. Aaltojen spektrit ovat olennaisen tärkeitä mm. koronan hiukkaskiihdytyksen mallinnuksessa, johon tulevissa tutkimuksissa myös keskitytään.
Keywords: Alfvén waves, wave propagation, wave-wave interactions, numerical methods, simulations, Solar corona, Solar wind